ASSESSMENT OF THE FUNCTIONING OF THE HOTEL FACILITY ON THE BASIS OF SUSTAINABLE DEVELOPMENT - ILNITSKA-GYKAVCHUK, G. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The need for the functioning of the hotel industry on the basis of sustainable development is due to the growing public attention to environmental issues, the need to reduce costs, save resources, increase the competitiveness of services provided. The essence and criteria of sustainable development of the hotel industry are revealed in the work. Sustainable development in the hotel industry requires a management system that combines three components: environmental protection, social issues, economics. To intensify the introduction of environmental innovations in hotels, their state support through preferential taxation, lending, legislative regulation, etc. is necessary. In order to green the activities in ecological hotels, it is advisable to implement various measures, including the use of environmentally friendly materials, renewable energy sources, technologies that save natural resources, use services, products of the local population, raise environmental awareness of staff and consumers and more. Based on the analysis, the strengths and weaknesses, opportunities and threats of eco-hotels were identified. The main obstacles to the introduction of sustainable development in the hotel sector are the low environmental awareness of society, as well as its poor awareness of environmental practices of hotels. Educational activities among society on sustainable development, economy and the prudent use of all resources are needed.